EXPLORING STUDENTS’ ABILITY AND PROBLEMS IN WRITING OPINION COLUMN PIECE - Taufik Afdal (SALEE: Study of Applied Linguistics and English Education, 2021)
The aims of this study are twofold. Firstly, it aims to explore English Education Department, STAI Miftahul Ulum Tanjungpinang students’ ability in writing opinion column piece. Secondly, it aims to investigate the problems faced by students when writing opinion column piece. A total of 10 students participated in this study. The research took place in January 2020. We used a test and a semi-structured interview to collect the data. The data were further analyzed using content analysis where the researcher scrutinized students’ works after they were given the task of completing an opinion column piece writing. In order to classify students’ ability, we adopted five indicators of writing opinion piece, namely: focus, ethos, pathos, logos and research and writing fluency. The study lead to the general findings that from the total of ten students, seven students fell under the category of average, three students fell under the category of good. Furthermore, most students expressed that generating ideas are difficult. The problems students faced and their detailed score are further elaborated on the paper.